La tarea inconclusa : América Latina integrada - Herrera, Felipe (Estudios Internacionales, 1973)
We believe that the dimension of an Integrated Latin America, in terms of its foundations, its difficulties and its internal and external projections, has not yet been sufficiently analyzed and understood, a limitation that has created a serious obstacle in a unifying process that to date It has been done rather under the sign of the geopolitical and technical-economic. The theory and practice for our effective integration are still "unfinished business." Fortunately, there is a history of this process that allows us to look at the future with optimism of these matters; on the other hand, we live today in an international and hemispheric scenario that allows us to intensifying them; and finally, there are formulas that allow us to revitalize the action that we must carry out, which should serve as the basis for programming a General Treaty on the Economic Integration of Latin America.